CtaA of Staphylococcus aureus Is Required for Starvation Survival, Recovery, and Cytochrome Biosynthesis - Clements, Mark O. (American Society for Microbiology, 1999)
A Staphylococcus aureus mutant (SPW3) apparently unable to survive long-term starvation was shown to have a transposon insertion within a gene homologous to ctaA of Bacillus subtilis which encodes a heme A synthase. Analysis of the cytochrome profiles of SPW3 revealed the absence of heme A-containing cytochromes compared to the parental 8325-4 strain. SPW3 demonstrated a 100-fold reduction in the ability to survive starvation induced by glucose limitation, under aerated conditions, compared to 8325-4. Analysis of starved cultures revealed that greater than 90% of the cells which demonstrated metabolism (as shown by rhodamine 123 accumulation) were unable to recover and form colonies on agar. Analysis of the lag phase and initial growth kinetics of those cells which could recover also showed a defect. This recovery defect could be partially alleviated by the inclusion of catalase in the recovery medium, indicating the probable involvement of oxidative stress. SPW3 also exhibited reduced colony size similar to that of a small-colony variant, increased resistance to aminoglycoside antibiotics, and reduced hemolysin and toxic shock syndrome toxin 1 production, but no alteration in the ability to form lesions in a subcutaneous mouse infection model.